2007
DOI: 10.1111/j.1752-699x.2007.00034.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of home mechanical ventilation on health‐related quality of life in patients with chronic alveolar hypoventilation: a prospective study

Abstract: NPPV improves HRQL, particularly in condition-specific areas. Improvements are related to effectiveness in ventilation. Side effects are common, but compliance is good and patient satisfaction is high.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 32 publications
2
22
0
Order By: Relevance
“…The majority of patients reported good HRQL. This is in keeping with other studies which have reported that HRQL in NIV users is as least as good as in those with other chronic health conditions 22,23 . Clearly, HRQL will be impacted significantly by the underlying condition leading to NIV requirement as well as comorbidities 6 .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The majority of patients reported good HRQL. This is in keeping with other studies which have reported that HRQL in NIV users is as least as good as in those with other chronic health conditions 22,23 . Clearly, HRQL will be impacted significantly by the underlying condition leading to NIV requirement as well as comorbidities 6 .…”
Section: Discussionsupporting
confidence: 89%
“…Although patient satisfaction with therapy is not widely reported, one other study has found similarly high rates 13 . A further study has shown high levels of satisfaction with therapy assessed on a categorical response scale although did not include patients with NMD or OHS 22 . Intuitively, satisfaction must be a major factor determining ongoing use of therapy; however, our study did not include people declining or ceasing treatment and so was not able to comment as to why some people are unable or unwilling to continue therapy.…”
Section: Discussionmentioning
confidence: 94%
“…Long-term mechanical ventilation (LTMV) is a wellestablished treatment for patients with hypercapnic chronic respiratory failure (HCRF) caused by various underlying disorders, such as chest wall deformities, neuromuscular disorders and obesity hypoventilation syndrome (OHS). [1][2][3][4] The total number of patients treated with LTMV in Europe has increased and will rise further with medical advances and the ageing of the population. 5 The treatment prevalence in Norway at the end of 2010 was 26.5/100 000.…”
Section: Introductionmentioning
confidence: 99%
“…H ome mechanical ventilation (HMV) is an established treatment for chronic ventilatory failure [1][2][3]. HMV improves survival and quality of life for selected patients with neuromuscular disease (NMD) [4][5][6] and kyphoscoliosis [7,8] and improves blood gas abnormalities and quality of life for obesity hypoventilation syndrome (OHS) [9][10][11] and cystic fibrosis [12,13].…”
mentioning
confidence: 99%